Wpływ obozów Fundacji Aktywnej Rehabilitacji na stan psychofizyczny osób po uszkodzeniu rdzenia kręgowego = The effect of foundation for active rehabilitation camps on psychophysical state following spinal cord injury - Kamińska-Gwóźdź, Ewelina; Lewicki, Romuald; Studnicki, Rafał; Opuchlik, Anna; Szłapińska, Joanna; Kubicki, Jacek; Włoch, Anna (Journal of Education, Health and Sport, 2015)
Kamińska-Gwóźdź Ewelina, Lewicki Romuald, Studnicki Rafał, Opuchlik Anna, Szłapińska Joanna, Kubicki Jacek, Włoch Anna. Wpływ obozów Fundacji Aktywnej Rehabilitacji na stan psychofizyczny osób po uszkodzeniu rdzenia kręgowego = The effect of foundation for active rehabilitation camps on psychophysical state following spinal cord injury. Journal of Education, Health and Sport. 2015;5(11):43-52. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33231 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A43-52 https://pbn.nauka.gov.pl/works/666326 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.09.2015. Revised 05.10.2015. Accepted: 30.10.2015. Wpływ obozów Fundacji Aktywnej Rehabilitacji na stan psychofizyczny osób po uszkodzeniu rdzenia kręgowego The effect of foundation for active rehabilitation camps on psychophysical state following spinal cord injury Ewelina Kamińska-Gwóźdź Instytut Fizjoterapii, Wydział Lekarski i Nauk o Zdrowiu, Uniwersytet Jana Kochanowskiego, Al. IX Wieków Kielc 19, Kielce Ewelina Kamińska-Gwóźdź Institute of Physiotherapy, Faculty of Medicine and Health Sciences, Jan Kochanowski University, Kielce Romuald Lewicki Katedra Fizjoterapii, Wydział Wychowania Fizycznego i Turystyki, Wszechnica Świętokrzyska, ul. E. Orzeszkowej 15, Kielce Romuald Lewicki The Department of Physiotherapy, Faculty of Physical Education and Tourism, Swietokrzyska Academy, Kielce Rafał Studnicki Zakład Fizjoterapii, Wydział Nauk o Zdrowiu z Oddziałem Pielęgniarstwa i Instytutem Medycyny Morskiej i Tropikalnej, Gdański Uniwersytet Medyczny, ul. Marii Skłodowskiej-Curie 3A, Gdańsk Rafał Studnicki The Unit of Physiotherapy, Faculty of Health Sciences Division of Nursing and the Institute of Maritime and Tropical Medicine, Medical University of Gdansk, Gdansk Anna Opuchlik Świętokrzyskie Centrum Onkologii, Zakład Rehabilitacji, ul. Artwińskiego 3, Kielce Anna Opuchlik Rehabilitation Institute, The Holycross Cancer Center in Kielce, Kielce Joanna Szłapińska Zakład Kształcenia Ustawicznego i Doradztwa Zawodowego, Wydział Studiów Edukacyjnych, Uniwersytet im. Adama Mickiewicza, ul. Wieniawskiego 1, Poznań Joanna Szłapińska Department of Continuing Education and Vocational Guidance, Faculty of Educational Studies, Adam Mickiewicz University in Poznań Jacek Kubicki Gabinet Fizjoterapii i Pediatrii, ul. Edmunda Łopuskiego 19a, Kołobrzeg Jacek Kubicki Physiotherapy and Paediatrics Office, Kołobrzeg Anna Włoch Wyższa Szkoła Ekonomii Prawa i Nauk Medycznych, Jagiellońska 109a, Kielce Anna Włoch High School of Economy, Law and Medical Sciences, Kielce Słowa kluczowe: uszkodzenie rdzenia kręgowego, Aktywna Rehabilitacja, sport, Fundacja Aktywnej Rehabilitacji. Keywords: spinal cord injury, Active Rehabilitation, sports, Foundation for Active Rehabilitation. Streszczenie Wstęp. Uszkodzenia rdzenia kręgowego są jednymi z najpoważniejszych dysfunkcji narządu ruchu skutkujące z reguły nieprzemijalnym stanem niepełnosprawności. Jest to stan o charakterze przewlekłym, który ma niekorzystny wpływ na sferę somatyczną, psychiczną oraz społeczną człowieka. Cel. Celem pracy było określenie wpływu obozu pierwszego stopnia Fundacji Aktywnej Rehabilitacji na stan psychofizyczny u osób po uszkodzeniu rdzenia kręgowego. Materiał i metody. Badania trwały od marca 2009 roku do marca 2010. Badaniami została objęta grupa 100 osób po uszkodzeniu rdzenia kręgowego. W pierwszym etapie badanie przeprowadzono przed obozem pierwszego stopnia organizowanym przez Fundację Aktywnej Rehabilitacji. W drugim etapie zbadano te same osoby trzy miesiące po ukończeniu powyższego obozu. Uczestnicy badań mieli ukończony 18 rok życia. Wśród badanych było 86 mężczyzn i 14 kobiet, w tym 33 osoby z uszkodzeniem rdzenia kręgowego w odcinku szyjnym, 57 osób z uszkodzeniem rdzenia w odcinku piersiowym, oraz 10 osób z uszkodzeniem rdzenia w odcinku lędźwiowym. Obozy odbywały się w Spale, w Zamościu oraz w Zielonej Górze. W badaniu wykorzystano kwestionariusz ankiety własnej konstrukcji dotyczący stanu psychofizycznego osób po uszkodzeniu rdzenia kręgowego. Wyniki. W wyniku uczestnictwa w obozie pierwszego stopnia u osób po uszkodzeniu rdzenia kręgowego nastąpiła poprawa stosunków międzyludzkich, wzrosła aktywność fizyczna, niezależność od innych osób, zwiększyła się ilość osób uprawiających sport oraz nastąpiła znaczna poprawa w czynnościach życia codziennego. Wnioski. Obóz pierwszego stopnia Fundacji Aktywnej Rehabilitacji wpłynął pozytywnie na stan psychofizyczny osób po uszkodzeniu rdzenia kręgowego. Dzięki działaniom Fundacji Aktywnej Rehabilitacji osoby z uszkodzeniem rdzenia kręgowego mają możliwość skorzystania z doświadczeń profesjonalnej kadry obozów, co przekłada się u badanych na postęp w zakresie zdolności motorycznych poprawiający nie tylko ich komfort życia, ale również ich stan psychiczny. Summary Introduction. Spinal cord injuries are among the most serious motor dysfunctions usually resulting in a permanent state of disability. It is a chronic condition with negative effect on the somatic, psychological and social state of humans. Purpose. The aim of this study was to determine the effect of participation in the introductory camps organized by the Foundation for Active Rehabilitation on psychophysical condition in individuals with spinal cord injury. Material and methods. Study was conducted between March 2009 and March 2010. It involved a group of 100 individuals suffering from spinal cord injury. In the first part of the study, research was conducted prior to the beginning of an introductory camp organized by the Foundation for Active Rehabilitation. The second part involved the same individuals three months after the camp. All study participants were 18 years of age or older and included 86 males and 14 females. Camps took place in Spala, in Zamość and in Zielona Góra. The study used custom-designed questionnaire concerning psychophysical status of individuals with spinal cord injury. Results. Improved relationships, increased physical activity, independence from other people, increased number of individuals practicing sports and a significant improvement in activities of daily life have been observed as a result of participation in the introductory camp for individuals with spinal cord injury. Conclusion. Foundation for Active Rehabilitation introductory camp had a positive effect on the psychophysical status of individuals with spinal cord injury. Through the effort of the Foundation for Active Rehabilitation, individuals with spinal cord injury can benefit from the experience of professional camp staff. Development of new motor skills further affects not only their comfort in life, but also their mental state.